Analysis Of Vibration Level Of A Perforated Panel Using Finite Element Method - Wai, Chee Mun; Putra, Azma; Ahmad Rivai (2012)
Introduction of perforation into plat-like structures is commonly found as one of practical noise control mechanisms to reduce the sound radiation. However, introduction of holes into the panel reduces its stiffness and hence increases its vibration. Since the effect is lacking, this paper investigates the dynamics of a perforated panel by using Finite Element Method (FEM). It is found that the size and number of holes determine the frequency range of which the level of vibration increases due to perforation.